Pengaruh Supervisi Akademik Terhadap Peningkatan Kompetensi Guru di Daerah 3T (Terdepan, Terpencil, Tertinggal) - Herry Sanoto; Soesanto Soesanto; A T Soegito; Kardoyo Kardoyo (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
The purpose of this study was to determine (1) the implementation of academic supervision in the 3T area in Bengkayang Regency; (2) the influence of academic supervision in the 3T (frontier, outermost, and least developes) areas in particular in Bengkayang Regency on improving teacher competence and professionalism. This research is a mix method research with the Sequential Exploratory model which is a combination research method between qualitative methods first and then strengthened by quantitative methods. The research subjects in this study were school supervisors, school principals and teachers in the Bengkayang Regency area, which were included in the 3T category. The instruments used in this study were interview guides, questionnaires and also observations. The results showed that (1) the process of academic supervision carried out in the 3T area in Bengkayang Regency could not be implemented according to the provisions proposed by the government, because there was limited access to locations with long distances between schools. Another problem with the academic supervision process in the 3T area is the lack of evaluation or feedback given by supervisors to teachers, so that the shortcomings of teachers cannot be conveyed properly. (2) The academic supervision program that has been implemented in Bengkayang Regency has no significant effect on increasing teacher competence and professionalism. Many other factors influence the competence and professionalism of teachers in the Bengkayang Regency area.